2013
DOI: 10.1021/jp403745q
|View full text |Cite
|
Sign up to set email alerts
|

On the Photoionization Spectrum of Propyne: A Fully ab Initio Simulation of the Low-Energy Spectrum Including the Jahn–Teller Effect and the Spin–Orbit Interaction

Abstract: The low energy photoionization spectrum of propyne (CH3-CCH), which reveals the vibronic structure of the propyne cation, is simulated using vibronic coupling theory. The spin-orbit interaction is included using an intensity borrowing approach, enabling determination of the (X̃(2)E1/2,3/2, v = 0) splitting and the relative photoionization intensity of these closely spaced levels. The results are compared with recent experimental studies and misstatements are corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 58 publications
4
23
0
Order By: Relevance
“…The optimized equilibrium geometry of the cation ground state was found to be of C s symmetry due to distortion resulting from a Jahn-Teller interaction. Note that a similar situation is encountered in the propyne cation ground state (CH 3 C 2 H + ) [34]. The calculated equilibrium geometries of neutral and cationic CH 3 C 3 N are detailed in Table 1 with the labels defined in Fig.…”
Section: Equilibrium Geometries and Vibrational Frequencies For The Ementioning
confidence: 72%
See 1 more Smart Citation
“…The optimized equilibrium geometry of the cation ground state was found to be of C s symmetry due to distortion resulting from a Jahn-Teller interaction. Note that a similar situation is encountered in the propyne cation ground state (CH 3 C 2 H + ) [34]. The calculated equilibrium geometries of neutral and cationic CH 3 C 3 N are detailed in Table 1 with the labels defined in Fig.…”
Section: Equilibrium Geometries and Vibrational Frequencies For The Ementioning
confidence: 72%
“…In CH 3 C 3 N + , we can suspect a spin-orbit splitting of the same order of magnitude, slightly decreased by the off-axis H atoms [43,44]. Thus, higher-resolved spectra of theX þ2 E X1 A 1 transition should exhibit a complex rovibronic structure due to the combination of the Jahn-Teller effect and spin-orbit coupling like in propyne [34,36] and the 2-butyne [45] cations. Pulsedfield-ionization zero-kinetic-energy photoelectron spectroscopy would be perfectly suited for this purpose.…”
Section: Resultsmentioning
confidence: 93%
“…[26], but in agreement with what is observed in the ground state of the acetylene radical cation (spin-orbit splitting of −30.86(44) cm −1 [27]). The calculations also indicated that the (E⊗e) Jahn-Teller effect in the ground state of the propyne radical cation is primarily linear, with a weak quadratic coupling and leads to a significant reduction of the spin-orbit coupling [23]. Given the structural similarities between the propyne and the 2-butyne radical cations, one may expect that the behaviour of the 2-butyne radical cation qualitatively resembles that observed for the propyne radical cation.…”
Section: Please Scroll Down For Articlementioning
confidence: 75%
“…No information has been reported on the magnitude of the spin-orbit interaction in the ground electronic state CH 3 -CC-CH + 3 so far, but it is well known that the spinorbit interaction and the Jahn-Teller effect need to be considered jointly in similar molecular systems [22][23][24][25]. A recent investigation of theX + 2 E ground state of the propyne radical cation by PFI-ZEKE photoelectron spectroscopy has revealed a spin-orbit splitting of about 13.2 cm −1 [26].…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation